HASIL TANGKAPAN ALAT TANGKAP BAGAN APUNG DI PERAIRAN TARUSAN, KABUPATEN PESISIR SELATAN, SUMATERA BARAT - Mohd. Yusuf Amrullah; Yogi Tri Sabtanto; Ahmad Ikbal Romadon (Universitas Muara Bungo, 2022)
The floating chart is one of the fishing gear that is widely used by fishermen where the main catch target is anchovies, while squid and other small pelagic fish are catch. The types of fish caught by the lift nets operating in Tarusan have not been recorded in detail and periodically, so it is necessary to record the types of fish caught by the lift nets operating in Tarusan waters. This research was conducted in March 2022 in Tarusan Waters, Pesisir Selatan Regency, West Sumatra. The research location is a place where fishermen make fishing with at the location of arrest I and location of arrest II. It was found that there were 12 species of fish caught at all research locations, but from the types of fish caught in the chart catch, at location I only 10 species of fish were found, while at location II, 11 species of fish were found, dominated by teri (Stolephorus sp).